MODERNIZATION OF THE VENTILATION SYSTEM OF AC LOCOMOTIVES VL80 - Varchenko, Ye. V.; Chumak, V. V.; Olivson, V. M. (Science and Transport Progress, 2008)
In the article the modernizations of a ventilation system of electric locomotives ВЛ80 by means of equipping them with converters ПСВ 50/16 for regulation of revolution frequency of engines of motor-fans are considered.